ANALISIS SHOOTING FUTSAL PUTRA PADA PERTANDINGAN LIGA PROFESIONAL 2021/2022 - Aldi Setiawan; Chairul Umam Ramadhan; Rafdlal Saeful Bakhri (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study discusses the analysis of basic shooting techniques and shooting areas for the Bintang Timur Surabaya team in the 2021/2022 proof-of-work league matches. The purpose of this study was to determine the basic technical abilities of the futsal shooting game in the Bintang Timur Surabaya team in the 2021/2022 professional futsal league and the dominant shooting and area shooting techniques carried out by the Bintang Timur Surabaya team. The method used is descriptive quantitative which later the data will be analyzed, processed and arranged to find existing problems. The source of the data taken was by watching the replay of the Bintang Timur Surabaya team in the second round which included an analysis of shooting techniques. The results of the analysis of the basic shooting techniques and shooting areas of the Bintang Timur Surabaya team during the second round. the total shot taken was 459 times, the instep was shot 300 times (65%), the toe was 48 times (11%) and the foot was shot 111 times (24%). Based on the results that have been done, it can be said that the characteristics of the shooting techniques carried out in Professional Futsal League matches use more of the instep. Shooting area (kicking area) The characteristics of the shooting area in the 2021/2022 Professional Futsal League match for the East Bintang Surabaya Team are as follows: a total of 459 shots were taken, with shooting in the weak area 214 times (47%) and shooting in the strong area as much as 245 times (53%). So it can be said that the characteristics of shooting techniques carried out in Professional Futsal League matches are mostly carried out in the strong area.